Laissez-Faire Leadership Style and its Implications on the Work Environment and Employee Performance in Public Organizations (A Study at the DKI Jakarta Education Office) - Nur Hasanah; Firra Fiqriyah; Ravica Sallza Azzahra; Aura Dhia Rizki Atthar; Safuan Safuan (CV. Publikasi Indonesia, 2026)
Leadership is a strategic factor in improving organizational effectiveness, particularly in public sector institutions where service quality and employee performance are closely linked to leadership practices. One leadership style often encountered in government organizations is laissez-faire leadership, which is characterized by minimal direct intervention from leaders and a high level of autonomy granted to employees in carrying out their tasks. While this leadership style may encourage independence and creativity, its effectiveness largely depends on the organizational context, especially the quality of the work environment. This study aims to analyze the effect of laissez-faire leadership on the work environment and employee performance at the DKI Jakarta Education Office. The research adopts a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to employees and subsequently analyzed using multiple linear regression techniques. The analysis focuses on examining both the direct and indirect relationships between leadership style, work environment, and employee performance. The results indicate that laissez-faire leadership has a significant influence on the work environment, particularly in terms of flexibility, interpersonal relationships, and perceived autonomy. Furthermore, the work environment is found to have a significant effect on employee performance. However, the direct impact of laissez-faire leadership on employee performance is relatively weak when not supported by a conducive work environment. Therefore, this study concludes that the work environment plays a crucial mediating role in strengthening the influence of laissez-faire leadership on employee performance in public sector organizations.